Ultrasensitive Multimodal Tactile Sensors with Skin‐Inspired Microstructures through Localized Ferroelectric Polarization. Issue 9 (24th January 2022) - Shin, Young‐Eun; Park, Yong‐Jin; Ghosh, Sujoy Kumar; Lee, Youngoh; Park, Jonghwa; Ko, Hyunhyub
Abstract: Multifunctional electronic skins have attracted considerable attention for soft electronics including humanoid robots, wearable devices, and health monitoring systems. Simultaneous detection of multiple stimuli in a single self‐powered device is desired to simplify artificial somatosensory systems. Here, inspired by the structure and function of human skin, an ultrasensitive self‐powered multimodal sensor is demonstrated based on an interlocked ferroelectric copolymer microstructure. The triboelectric and pyroelectric effects of ferroelectric microstructures enable the simultaneous detection of mechanical and thermal stimuli in a spacer‐free single device, overcoming the drawbacks of conventional devices, including complex fabrication, structural complexity, and high‐power consumption. Furthermore, the interlocked microstructure induces electric field localization during ferroelectric polarization, leading to enhanced output performance. The multimodal tactile sensor provides ultrasensitive pressure and temperature detection capability (2.2 V kPa −1, 0.27 nA °C −1 ) over a broad range (0.1–98 kPa, −20 °C < Δ T < 30 °C). Furthermore, multiple simultaneous stimuli can be distinguished based on different response times of triboelectric and pyroelectric effects. The remarkable performance of this sensor enables real‐time monitoring of pulse pressure, acoustic wave detection, surface texture analysis, and profiling of multiple stimuli. Abstract : Inspired by the structure and function of human skin, an ultrasensitive self‐powered multimodal sensor is demonstrated based on an interlocked ferroelectric copolymer microstructure. The triboelectric and pyroelectric effects of ferroelectric microstructures enable the simultaneous detection of mechanical and thermal stimuli in a single device, demonstrating potential applications in humanoid robots, wearable devices, and healthcare systems.